Factors associated with opioid overdose during medication-assisted treatment: How can we identify individuals at risk? - Vivian Y. O. Au; Tea Rosic; Nitika Sanger; Alannah Hillmer; Caroul Chawar; Andrew Worster; David C. Marsh; Lehana Thabane; Zainab Samaan (BMC, 2021)
Abstract Background Due to the loss of tolerance to opioids during medication-assisted treatment (MAT), this period may represent a time of heightened risk for overdose. Identifying factors associated with increased risk of overdose during treatment is therefore paramount to improving outcomes. We aimed to determine the prevalence of opioid overdoses in patients receiving MAT. Additionally, we explored factors associated with opioid overdose during MAT and the association between length of time enrolled in MAT and overdose. Methods Data were collected prospectively from 2360 participants receiving outpatient MAT in Ontario, Canada. Participants were divided into three groups by overdose status: no history of overdose, any lifetime history of overdose, and emergency department visit for opioid overdose in the last year. We used a multivariate multinomial regression model to assess demographic and clinical factors associated with overdose status. Results Twenty-four percent of participants reported a lifetime history of overdose (n = 562), and 8% reported an emergency department (ED) visit for opioid overdose in the last year (n = 179). Individuals with a recent ED visit for opioid overdose were in treatment for shorter duration (odds ratio [OR] 0.92, 95% confidence interval [CI] 0.87, 0.97, p = 0.001). Individuals with a lifetime or recent history of overdose were more likely to be younger in age (OR 0.93, 95% CI 0.89, 0.98, p = 0.007 and OR 0.84, 95% CI 0.77, 0.92, p < 0.001, respectively), report more physical symptoms (OR 1.02, 95% CI 1.01, 1.03, p = 0.005 and OR 1.03, 95% CI 1.01, 1.05, p = 0.005, respectively), and had higher rates of non-prescription benzodiazepine use (OR 1.87, 95% CI 1.32, 2.66, p < 0.001 and OR 2.34, 95% CI 1.43, 3.81, p = 0.001, respectively) compared to individuals with no history of overdose. Conclusions A considerable number of patients enrolled in MAT have experienced overdose. Our study highlights that there are identifiable factors associated with a patient's overdose status that may represent areas for intervention. In particular, longer duration in MAT is associated with a decreased risk of overdose.